Data from: Hyperabundant herbivores limit habitat availability and influence nest-site selection of Arctic-breeding birds - Flemming, Scott A.; Nol, Erica; Kennedy, Lisa V.; Smith, Paul A. (Dryad, 2020)
1. Understanding an organism’s habitat selection and behavioural
flexibility in the face of environmental change can help managers plan for
future conservation of that species. Hyperabundant tundra-nesting geese
are influencing Arctic environments through their foraging activities.
Goose-induced habitat change in Arctic wetlands may influence the
availability of habitat for numerous shorebird species that breed
sympatrically with geese. 2. Here, we explore whether goose-induced
habitat alteration affects shorebird breeding density and nest-site
selection. Using habitat data collected at sites with high, moderate, and
low goose influence, and samples collected during two periods separated by
11 years, we document the habitat characteristics influenced by geese. We
describe the habitat characteristics preferred by shorebirds and relate
their availability to goose influence and shorebird density. Finally, we
examine whether shorebird nest-site selection has changed over time and
whether shorebirds select nest sites differently in habitat influenced by
geese. 3. We report spatial and temporal changes in sedge meadow habitat
and lateral concealment relating to goose influence. The availability of
sedge meadow habitat and the degree of lateral concealment declined with
increasing goose influence, and also declined at two sites over the 11
years of the study. 4. Densities of both cover- and open-nesting
shorebirds were highest where goose influence was lowest. At sites with
low goose influence, cover-nesting shorebirds selected nest sites with
more sedge meadow and concealment than at sites with moderate and high
goose influence, presumably because these high quality sites were more
available. 5. Synthesis and applications. Our results suggest that
goose-induced habitat alteration is influencing the availability of
preferred habitat, and the densities of sympatric-nesting shorebirds.
Cover-nesting species that prefer moist sedge habitat may be especially
susceptible to goose-induced alteration, while upland specialists may be
unaffected. Our results underscore the need for management of Arctic goose
populations to reduce their impacts on sedge meadow habitats. Studies
examining the degree to which these effects scale up to impact the
population sizes of declining shorebirds should be considered a future
research priority.
Proportional cover and dominant habitat type surveysHabitat surveys
conducted at all shorebird nests and random sites. Includes proportional
cover of different habitat types and dominant habitat
type.dryas_1.csvCover types and heights of cover typesCover types and
heights of all cover types measured at random sitesdryas_2.csv
Keywords: nest-site selection; snow goose; overabundant population; habitat availability; Community Ecology < Substantive Area; Ross' goose